STRATEGI PENGELOLAAN DATABASE UNTUK MENUNJANG KEAMANAN DAN EFEKTIVITAS SISTEM INFORMASI MANAJEMEN - Firza Azzahra; Muhammad Irwan Padli Nasution (INTERNATIONAL, Journal of Sharia Business Management, 2025)
In today’s digital era, data has become a critical asset for every organization. All operational activities and decision-making rely heavily on how this data is managed. In this context, databases serve as the central storage and management hub, serving as the foundation of Management Information Systems. However, issues such as data security and management effectiveness often pose challenges. This study examines how sound database management strategies can help maintain security and improve effectiveness in Management Information Systems. With optimal database management, organizations not only protect data from the risk of data breaches but also manage information quickly and accurately to support better decision-making.